Cover Image, Volume 13, Issue 1. Issue 1 (12th May 2020) - Unknown
Abstract : On the cover : Genomic selection can be implemented in lentil to make within‐population and across‐environment predictions. See Haile et al (https://doi.org/10.1002/tpg2.20002 ).